2020
DOI: 10.1097/tp.0000000000003248
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcomes and Survival in Moderate-severe Portopulmonary Hypertension After Liver Transplant

Abstract: Background. Portopulmonary hypertension is present in an estimated 5.3% to 8.5% of liver transplant candidates. Untreated, 5-year survival is estimated between 14% and 28%. Moderate-severe disease is a contraindication to liver transplant due to the high perioperative mortality, but patients optimized with pulmonary vasodilator therapy can become eligible for transplant. There is minimal data regarding posttransplant outcomes and ability to discontinue pulmonary vasodilator therapy posttransplant. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 39 publications
1
19
1
Order By: Relevance
“…Included studies that reported survival data from a minimum of 20 patients. (14,(27)(28)(29)(30)32) *Unpublished data. Abbreviations: PH, pulmonary hypertension; N/A, not applicable.…”
Section: Discussionmentioning
confidence: 99%
“…Included studies that reported survival data from a minimum of 20 patients. (14,(27)(28)(29)(30)32) *Unpublished data. Abbreviations: PH, pulmonary hypertension; N/A, not applicable.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, transjugular intrahepatic portosystemic shunt placement has no role in the management of PoPH and may increase right ventricular preload and precipitate right heart failure [10]. Careful patient selection and preoperative optimisation of PoPH are associated with a 5-year post liver transplant survival of 78- [6,15].…”
Section: Discussionmentioning
confidence: 99%
“…51,52 A single-center experience of 24 POPH patients with excellent outcomes was published by the University of Wisconsin group. 53 All patients were optimized on medical therapy with 1-, 3-, and 5-year survival rates of 96%, 91%, and 91% in the cohort that underwent transplant. Of those receiving parenteral PAH therapy, all were weaned during a median time of 7 months.…”
Section: Special Populations and Topicsmentioning
confidence: 99%